Enforcement of Reduced Punishment for Perpetrators of Terrorism Crimes against Death Penalty Punishment - Serbabagus, Shalahudin; Andreianto, Frifqi Dewangga; Munir, Ahmad; Hudi, Moh. (Universitas Muhammadiyah Tangerang, 2024)
Terrorism is one of the crimes that fall under the death penalty category. The threat of the death penalty for perpetrators of criminal acts of terrorism as a tool to enforce the law. However, there are conflicting rules between the death penalty and human rights. So, can the death penalty be changed to life imprisonment? This research aimed to analyse whether reducing punishment for those convicted of terrorism could be enforced. This research uses a normative research method with a statutory, conceptual, and case approach through judge decisions relating to terrorism cases. The implementation of Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism considers acts of terrorism to be a threat to ideology and national security. The death penalty is imposed as a last resort to protect society and can be carried out after a prisoner's request for pardon is rejected by the President. Legal efforts that can be taken to reduce terrorism punishment range from filing an appeal, cassation, and judicial review to the final application to ask for forgiveness from the President, who is the convict's only hope of reducing the sentence to obtain human rights protection and legal relief.